The Study on the Treatment of Endometritis by Gentamisin in Cows - Apaydın, A. Mükremin; Kalkan, Cahit; Ocal, Halis; Deveci, Hüseyin; Timurkan, Hüseyin (Van Yüzüncü Yıl Üniversitesi, 1991)
Eighty-six cows which were diagnosed wilh endometritis by clinical and histopathological  examinations, were used as a matetial. The number of the cows in the first, second and third grades of endometritis were 53, 24 and 9, respectively. All of cows were treated wilh intrauterin infussion of 5oo mg Gentamicin sulphate in 40 ml distillated water daily for three days. After treatment, in the first three inseminations, 42 of first (79.2 %), 17 of second (70.8 %), 8 of third (88.8 %) grades of endometritis, and totally 67 (77.9 %) cows conceived.

Klinik ve histopatolojik muayenelerle endometritis teşhis edilen 86 inek materyal olarak kullanıldı. Bunlardan 53'ü I. derece, 24'ü 2. derece, 9'u da 3. Derece endometritisli idi. Bütün ineklere günlük 500 m g Gentamisin sülfat, 40 m/ distile su içinde 3 gün sureyle, intra uterin verildi. Tedavi sonrasinda, ilk 3 tohumlama I.derece endametritisli 42 ( %79.2), 2. derece em'li 17 (%70.8) ve 3.derece em.li 8 (% 88.8) olmak üzere toplanı 67 (%77.9) inek gebe kaldı.
İNEKLERDE ENDOMETRİTİSİN GENTAMİSİN'LE TEDAVİSİ ÜZERİNE ÇALIŞMA